The Study of Condition of the South Bug River Basin with Using Geoecological Methods - Zalizniak, Y. I. (Man and Environment. Issues of Neoecology, 2020)
Purpose. Assess the current state of the Southern Bug River basin and the degree of anthropogenic impact on it (transformation) Methods. The methodology of complex field geographic research (according to S. Kurlov) was chosen for the research. On its basis, water samples were taken at the appropriate points of the river basin, which directly covered the Southern Bug River itself, as well as its tributaries, and the composition of coastal soils was analyzed. Laboratory experiments were performed on the basis of a licensed laboratory of the Uman National University of Horticulture Results. Based on the analysis of the data set of the main hydrochemical indicators of the surface water quality of the Southern Bug river basin and the analysis of the soil, it was found at some experimental points that the MPC content of the studied indicators was exceeded. The content is exceeded at all sampling points, due to the high content of complexes with humic acid salts, secondary waterlogging of reclaimed lands. The nitrite content is exceeded in the following places: r. Southern Bug (Vinnitsa and Ladyzhin), r. Ustya (Nemyriv), r. Udych litskiy district) and r. Dohna (Bershad district). The main reason for the intake of nitrates into the water is the washout of fertilizers from fields and vegetable gardens. All surface water bodies have increased water hardness, its acidity is within normal limits. The soils adjacent to the streams under consideration bear clear signs of hydrogenic accumulation of substances (carbonates, gypsum, salts) and deltaic conditions of formation (horizontal stratification, horizons buried, remnants of freshwater fauna). Conclusions. The concentration of pollutants increases with the approach of the tributaries of the Southern Bug River and the relief formed by them to their base of erosion. Excess concentrations of alkaline hydrolyzed nitrogen, as well as phosphorus and potassium compounds at the sampling points indicate a high level of intensity of the farming system, in which the use of agrochemicals is given priority. However, long-term ingress of these compounds into the water body will accelerate the process of eutrophication in the near future. The loss of humus in the soils of agricultural lands adjacent to the rivers Sob, Dokhna, Ustya was revealed. In general, the geosystem of the Southern Bug River suffers from a complex anthropogenic impact, the main source of which is agricultural production. (Tep-